AEU Women's Enquiry, 1945 (pg. 1) (1945)
1945 1939-1945 "AEU Women's Enquiry, 1945 (pg. 1)" [hfr0171], 1945 While preparing its evidence for the Royal Commission on Equal Pay, the Amalgamated Engineering Union launched an enquiry in 1944 into the position and opinions of its women members. A report entitled 'Women in Post-War Industry' was published in April 1945. This extract shows that, despite the low participation in the Enquiry, the Union concluded that the majority of women working in engineering would prefer to stay in the industry after the war.